Feasibility and acceptability of a home‐based resistance training intervention in adolescent and young adult hematopoietic cell transplant survivors. Issue 11 (14th July 2021) - Ketterl, Tyler G.; Ballard, Sheri; Bradford, Miranda C.; Chow, Eric J.; Jenssen, Kari; Myers, Sam; Rosenberg, Abby R.; Van Doren, Matt; Baker, K. Scott
Abstract: Background: Adolescent and young adult (AYA) hematopoietic cell transplantation (HCT) survivors are at increased risk of metabolic syndrome and lean body mass (LBM) deficits. Resistance training (RT) is a potential intervention to improve LBM, metabolic fitness, and reduce risk of cardiovascular disease. Procedure: Eligible participants ages 13–39 years, 80–120 days post‐HCT, transfusion independent, and prednisone dose ≤1 mg/kg/day were approached. Baseline assessments of body composition (DXA), anthropometrics, and strength testing were completed and participants were taught a 12‐week, home‐based RT intervention with weekly remote coaching. Follow‐up assessments were at day +200 (FU1) and +365 post‐HCT (FU2). Feasibility targets were (a) 60% enrollment of approached patients, (b) 80% completion of weekly phone calls, and (c) 80% completion of the RT intervention and FU1 assessments. Acceptability was based on positive responses in qualitative interviews. Results: Twenty of 31 (65%) eligible AYAs enrolled. Three participants failed to complete baseline measurements (2 = scheduling barriers, 1 = passive refusal) and four participants who completed baseline assessments did not receive the intervention (1 = medical reasons, 2 = no longer interested). Of those who completed baseline assessments, 13 received the intervention, completed 88.5% of coaching calls, and 11 (65%) completed FU1. LBM (kg) increased or remained unchanged in nine of nine participants with complete body composition data at FU1 (mean 1.1 kg; 95%CI: 0.4, 1.9). All participants who completed FU1 reported they would recommend the intervention to an AYA HCT survivor. Conclusions: A home‐based RT intervention in AYA HCT survivors early post HCT is both feasible and acceptable and may maintain or increase LBM.